A Highly Red‐Emissive Lead‐Free Indium‐Based Perovskite Single Crystal for Sensitive Water Detection. Issue 16 (12th March 2019) - Zhou, Lei; Liao, Jin‐Feng; Huang, Zeng‐Guang; Wei, Jun‐Hua; Wang, Xu‐Dong; Li, Wen‐Guang; Chen, Hong‐Yan; Kuang, Dai‐Bin; Su, Cheng‐Yong
Abstract: Low‐dimensional luminescent lead halide perovskites have attracted tremendous attention for their fascinating optoelectronic properties, while the toxicity of lead is still considered a drawback. Herein, we report a novel lead‐free zero‐dimensional (0D) indium‐based perovskite (Cs2 InBr5 ⋅H2 O) single crystal that is red‐luminescent with a high photoluminescence quantum yield (PLQY) of 33 %. Experimental and computational studies reveal that the strong PL emission might originate from self‐trapping excitons (STEs) that result from an excited‐state structural deformation. More importantly, the in situ transformation between hydrated Cs2 InBr5 ⋅H2 O and the dehydrated form is accompanied with a switchable dual emission, which enables it to act as a PL water‐sensor in humidity detection or the detection of traces of water in organic solvents. Abstract : Unleaded and unleashed : A highly emissive lead‐free indium‐based perovskite single crystal, Cs2 InBr5 ⋅H2 O, was successfully prepared. The versatile material is the first reversible metal halide perovskite photoluminescence water sensor and paves the way for the application of metal halide perovskites in water detection.